Experimental characterisation and constitutive modelling of transparent polyurrethane - Mokarram Hossain (UKACM Annual Conference 2019, 2019)
Transparent polyurethane has been widely applied in laminated windshield glasses as the interlayer material to enhance the reliability due to its outstanding impact resistance. Under impact loading such as bird strike, the interlayer undergoes large tensile deformation at wide range of strain rates. In addition, the interlayer is on service over a wide range of temperatures for a plane traveling around the world. The mechanical behavior of transparent polyurethane under these conditions is not fully understood. In this study, systematical experiments were performed on transparent polyurethane. The viscoelasticity of the material was firstly verified by several quasi-static cyclic tests. Then a series of large tensile deformation and tensile failure experiments were conducted under various strain rates using a servo- hydraulic high-speed tensile machine. All strain data were acquired by the Digital Image Correlation (DIC) technique. The experimental results show that tensile stress-strain curves and failure behaviour are significantly temperature and strain rate dependent. Finally, a phenomenological-based finite strain viscoelastic model is developed. After parameter identifications, one-dimensional equations are fitted to experimental data that yield good predictions.